Knowledge, Attitude and Practice regarding Polycystic Ovarian Syndrome(PCOS) among final year medical students and interns in a Medical College in Kathmandu Nepal - Adhikari, P.; Bhattarai, J. (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrinal conditions in young women. It affects women in their reproductive years. This study was undertaken to find out understanding of PCOS in young doctors who will be shortly delivering health services in the community. Methods: This will be a Descriptive, Cross-sectional study carried out in Nepal Medical College Teaching Hospital on the final year medical students of MBBS and interns. Survey was done online using Google docs questionnaire. A set of questionnaire adopted from similar study was used. The questionnaire had 3 sections, testing knowledge, attitude and practice. A total of 117 study participants were enrolled in the study. Data was tabulated and analyzed. Descriptive statistics was used to calculate frequency and percentage of variables. Results: There were 61 (52.13%) female, and 56 (47.86.%) were male who participated in the study. The median age of the population was 23 years. The population’s age range was 10 years, with the youngest person being 20 and the oldest person being 30. Majority (98%) had heard about the ovarian cyst before, and 74.4% had received knowledge through friends. All participants (100%) chose to comfort and counsel their friend regarding treatment modalities; in response to if she reveals her diagnosis to them.76.92% thought that PCOS patient will hide their diagnosis. 92.30 % of the study participants responded positively for weight reduction as an option for management with 72.72 % identified it to help in countering insulin resistance. 96.58% of them responded to lack of authentic material for PCOS awareness and 85.47% of them thought that awareness can be raised through social media. When asked about best person to treat PCOS, 85.47% responded to Gynecologist. Conclusion: The final year medical students and interns demonstrated a satisfactory level of polycystic ovary syndrome knowledge and had a good attitude towards disease with good practice knowledge for disease.